Study Of Antibiotic Susceptibility of Clostridium Difficile Isolated from Childhood Diarrhea and Detection of BlaCTX-M Gene - Khorshed, Aevar Ashraf (American Journal of Biology and Natural Sciences, 2025)
Background & aim: Clostridium difficile is the most frequent cause of antibiotic-associated diarrhea in hospitals and other healthcare settings. This is a serious problem due to rising rates of morbidity and mortality as well as rising health care expenses. Therefore, the current study aimed to evaluate the resistance of Clostridium difficile isolated from the digestive system against several antibiotics and to detect the BlaCTX-M gene responsible for the bacterial resistance to beta-lactamase antibiotics. Materials and methods: The study collected 280 stool samples from patients who were admitted to Kirkuk Hospital in Kirkuk City between October 2024 and February 2025 after visiting a specialist physician and referring them to the laboratory. Every sample's information was obtained. Following direct transportation to the lab, the samples were cultivated on blood and MacConkey agar media and incubated for 24 hours at 37°C in order to detect genes and test for antibiotic sensitivity. Results: The findings were found that 187(66.8%) of total samples were appear as positive results for bacterial growth. The results of the identification revealed that among the 280 cultured stool samples 187 samples gave positive culture with bacterial isolates from patiens with diarrhea, E. coli represent 48.7% of the isolated bacteria. Followed by. 18.2% Klebsiella spp., 13.8% Pseudomonas aeruginosa, 8.0% Clostridium difficile, 15.9% Shigella spp., 4.3% Serratia marcescens, 1.1% Actinomycetes bovis. C. difficile was low sensitive to Levofloxacin 33.3%, Vancomycin 26.7%, Clindamycin 40.0%. While it was highly sensitive to Gentamicin 66.7% and Amikacin 86.7%. After isolating DNA from C. difficile using an extraction and electrophoresis kit, it was found that 91.7% of C. difficile isolates contained the BlaCTX-M gene. Conclusions: it was found that C. difficile is considered one of the causes of diarrhea in many children, and it is characterized by its high resistance to antibiotics, which is aided by its possession of antibiotic resistance genes, including the BlaCTX-M gene, which was identified in most of the isolates obtained.